Study on the Load Transfer Behaviour and Bond-Slip Model of Fully Grouted Rockbolt - Shuisheng Yu; Honghao Yang; Jin Chen; Yawei Wang; Shucan Lu (Shock and Vibration)
Rockbolts are often subjected to loads during service, and the load transfer behaviour of rockbolts is very important. Therefore, in this study, pullout tests were performed on two kinds of rockbolt systems, with and without defects, and the load transfer behaviour and failure modes were analysed. According to the load transfer process between the rockbolt and cement mortar interface, a bond-slip model considering the yield of the rockbolt was proposed, and the nonlinear behaviour in the softening stage was considered. The test results showed that the evolution of the interface load between the rockbolt and cement mortar in the grouted rockbolt systems without defects underwent four stages of gradual failure, namely, elasticity, yield, softening, and complete slip, and its failure mode involved the rockbolt being pulled out accompanied by splitting cracks and tensile cracks on the concrete surface. The proposed bond-slip models considering the nonyielding and yielding of the rockbolt can accurately reflect the actual load transfer behaviour of a fully grouted rockbolt.